1987
DOI: 10.1111/j.1365-2125.1987.tb03240.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bronchial asthma with terfenadine; a randomized controlled trial.

Abstract: 1 Terfenadine, a histamine H1-receptor antagonist, was studied in 52 patients with stable mild perennial asthma with an allergic basis. 2 After a placebo run-in period, patients were randomly allocated to either terfenadine 120 mg twice daily or placebo. After 2 weeks they were crossed over to the other treatment. Forty-six patients completed the study. 3 Terfenadine was significantly more effective than placebo as measured by peak expiratory flows and by symptom scores. 4 These results suggest that histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

1988
1988
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 18 publications
(17 reference statements)
2
30
2
Order By: Relevance
“…The results of both Taytard et al (1987) and Rafferty et al (1987) using terfenadine accord well with our own experience with azelastine. Further work is required to elucidate whether the clinical improvement which we recorded was solely attributable to the potent Hl-receptor antagonism of azelastine or to an additional 'anti-allergic' activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of both Taytard et al (1987) and Rafferty et al (1987) using terfenadine accord well with our own experience with azelastine. Further work is required to elucidate whether the clinical improvement which we recorded was solely attributable to the potent Hl-receptor antagonism of azelastine or to an additional 'anti-allergic' activity.…”
Section: Discussionsupporting
confidence: 87%
“…However, newer non-sedating antihistamines such as terfenadine (Sorkin & Heel, 1985) are now being used to assess the value of HI-receptor blockade in asthma since higher doses can now be used without the occurrence of unwanted effects. Indeed Taytard et al (1987) have recently shown terfenadine to be significantly more effective than placebo in reducing symptom scores and increasing peak expiratory flow rates in mild extrinsic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protecting against the bronchoconstrictor effect of inhaled allergen, antihistamines have been shown to cause bronchodilatation in asthmatic subjects following single [13] or repeated administration [25]. It is difficult to explain the absence of a bronchodilator effect in our study, but may reflect the type of asthmatic subjects enrolled.…”
Section: Discussioncontrasting
confidence: 46%
“…Correspondence: Dr C. Teale, Pulmonary Function Laboratory, Killingbeck Hospital, York Road, Leeds, LS14 6UQ (Gould et al, 1988;Taytard et al, 1987).…”
Section: Methodsmentioning
confidence: 99%